ENDOCRINAL DISORDERS: ETIOLOGY AND PATHOGENESIS. DYSFUNCTIONS OF THE SEXUAL GLANDS - P. F. Litvitskii ("Paediatrician" Publishers LLC, 2012)
The issues of etiology, pathogenesis, clinical manifestations and development mechanisms of the most common forms of endocrinalregulation of the sexual glands, impairments of the puberty in girls and boys and sexual dysfunction in women and men are analyzed in the article.